Remote TELEmonitoring and Health Coaching for patients with acute heart failure: results of the TELE-HC randomized trial. (25th November 2020) - Schulte, P; Olson, L; Bruce, C
Abstract: Introduction: Patients discharged after acute decompensated heart failure (ADHF) have elevated risk for readmission due to multiple factors including suboptimal behavioral and social support. Telemonitoring interventions have shown inconsistent effectiveness in reducing HF readmissions. Patient-centered health coaching, when combined with telemonitoring, may be a viable model to engage patients in self-care behaviors and enhance patient experiences following acute hospitalization. Purpose: This multicenter randomized trial evaluates whether remote telemonitoring combined with health coaching decreases 60 day readmission rates for patients with ADHF when compared to standard of care. Methods: Patients with primary or secondary diagnosis of ADHF were consented and randomized prior to hospital discharge to either standard care or intervention of remote telemonitoring and health coaching. Within 2 days of hospital dismissal, intervention patients were onboarded to the remote monitoring platform, which links personal health sensors which collect on-body physiologic measures (ECG, heart rate, respiration rate, and activity via 3-axis accelerometer) with providers through secure mobile communication. A registered nurse was designated as the primary health coach focusing on disease management - including symptom recognition, adherence to treatment strategies, care coordination, medication matters, and problem solving. A social worker and nutritionist were also assigned. The primary outcome was all-cause mortality or readmission within 60 days of hospital dismissal. Statistical analysis included stratified log-rank tests and stratified Cochran-Mantel-Haenszel Chi-square test to account for site-stratified randomization. Results: The study was halted due to low rate of subject accrual. Of planned 304 subjects, 143 were randomized between 2015 and 2019 at 6 sites in the United States. Dropout and withdrawal after randomization of 32 subjects (22%) left 112 analyzable for the primary endpoint. Many subject withdrawals after unblinded disclosure of arm allocation were related to treatment assignment. Immediate withdrawal without follow up in these subjects precluded an intention-to-treat analysis. Mean age was 69 years and subjects were more often male (56%) and non-Hispanic white (70%). In per-protocol analysis, using subjects adherent to protocol specified visits (n=112), we observe no difference in the primary outcome (26% among intervention vs 28% among standard care, Figure, p=0.77). There were also no differences among secondary outcomes of overall mortality (2% vs 7%, p=0.20) or composite emergency department visit, hospital admission, or death (35% vs 34%, p=0.85). Conclusions: Among patients with heart failure, an intervention of remote telemonitoring and health coaching did not reduce all-cause readmission or mortality. Significant withdrawal rates suggest future studies may need to improve screening and study retention. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Institutes of Health, National Institute on Aging